Transnational law and local struggles : mining, communities and the World Bank - Szablowski, David (Hart monographs in transnational and international law., 2007)
The global spread of transnational mining investment, which has been taking place since the 1990s, has led to often volatile conflicts with local communities. This book examines the regulation of these conflicts through national, transnational and local legal processes. In doing so, it examines how legal authority is being redistributed among public and private actors, as well as national and transnational actors, as a result of globalizing forces. The book presents a case study concerning the negotiation of land transfer and resettlement between a transnational mining enterprise and indigenou.